The Mevlana Example in the Universal Islam Concept - SÖNMEZ, Vecihi (Scientific Journal of Faculty of Theology, 2017)
In the dark lights of the political and communal misconceptions of the world in the 7th/13th centuries a number of things were written and said about the enlightening Mevlana who came up with his model life and who has hugged the whole humanity with his love, thoughts and accomplishments. In the duration of his life undertaking the great consistencies, and after his death in order to systemise his teachings a religious order called “Mevlevilik” including the thoughts and beliefs was formed, his achievements firstly to the Ottoman geography were scattered to the entire world, in order to understand and explain his universal teaching about every century great efforts were spent, his achievements were translated into various languages of the world, and a number of annotations were made. The famous achievement of Mevlana called Mesnevi entirely consists of Qur’an and Sunnah, in his couplets he continuesly makes moral quotations from the verses, “as I am in my dear body I am the slave of Qur’an. I am the soil of the road of the God’s selected prophet Muhammed. Who ever transfers more from me apart from this word, I am disgusted both from this word and the person who said it. Mevlana with these words of his; conveys that Allah says to humanking that in order to understand the relationship between man and universe man should benefit from the universal Islam concept, and announces that cases in which do not suit these two bases will be far from the imputations to be made. In short words to express ,the teachings of Mevlana consists of the facts that the religions in which ignores the certain rules of Islam are not superior, Islam counts every religion of the world a universal source of order, accepts every creation of Allah as servants God, and approaches the religions of Islam as the last religion which embaresses Tauheed, and invites the whole humanity to cope up with the universal values and in consistency of serving God. The approachment of Mevlana without distinguishing man with the invitation as come and drink the water of the mercy fountain is basically an approachment of the religion Islam and the Qur’an as ‘Oh people come together to the peace’. Just as the famous thinker Irene Melikoff points out:”if all the world’s nations translates the achievements of Mevlana into their own language there won’t be any evilness, hate, grudge and war left in the world”. According to Mevlana, in the Islam concept as the nonbelief (abuse) are considered as the biggest of all crimes, it is considered to be between the slave and God it is stated that the punishments of these kinds of crimes are postponed to the hereafter. With the movement from this principle, in social, moral and lawfull relations, the humanity qualities are taken into considerations. According to this understanding, it is not the person who is wicked it is the actions of the person which is wicked. Meanwhile it is the unions between Muslims and the holy book in consideration. Besides, Muslims, Christians and Jews accepts Hz.Ibrahim as a prophet. In that manner from the celestical religion members, it is expected that they come forward with their alliance apart from their theologic and historical difference in opinion.